Reslip of a Previously Fixed Slipped Upper Femoral Epiphysis with an Associated Vitamin D Deficiency. (17th February 2014) - Haque, Aziz Ul; Bloch, Benjamin; Abraham, Alwyn
Abstract : Slipped upper femoral epiphysis (SUFE) is a relatively common adolescent hip disorder that represents a biomechanical instability of the proximal femoral growth plate. A link between vitamin D deficiency and SUFE has emerged in recent years; however, we present a unique case of a 10-year-old girl who presented with a reslip of a previously fixed SUFE with an associated vitamin D deficiency.